Use of City Region Food Systems Toolkit by Tamale City, Ghana - CGIAR Research Program on Water, Land and Ecosystems (2021)
Tamale City in Ghana is making use of climate change vulnerability assessments and applying the City Region Food Systems (CRFS) Toolkit to strengthen food security